Space, time, world - Fortescue, Michael D. 1946- (John Benjamins Publishing Company, 2024)
This book aims to relate and unify the concepts of SPACE and TIME in the concept of WORLD. The book will be of interest to all students and practitioners of Linguistics, in particular Cognitive Linguistics and Linguistic typology, but also to a more general readership interested in the historical evolution of concepts of SPACE and TIME.